2020
DOI: 10.1521/pedi.2020.34.supp.122
|View full text |Cite
|
Sign up to set email alerts
|

Dos and Don'ts in Treatments of Patients With Narcissistic Personality Disorder

Abstract: This article identifies guiding principles in effective psychotherapies of patients with narcissistic personality disorder (NPD) and cautions against some common pitfalls. Individual psychotherapies of NPD patients were examined by both authors, who tested whether or not some principles, recommended in the literature, effectively promote these therapies and help these patients in moving forward with their lives and with effective therapy use. The authors identify a number of principles that were associated wit… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
73
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
8

Relationship

2
6

Authors

Journals

citations
Cited by 30 publications
(73 citation statements)
references
References 79 publications
(87 reference statements)
0
73
0
Order By: Relevance
“…A nuanced approach to narcissistic presentations, informed by tendencies towards grandiosity and/ or vulnerability, and awareness of their potential impact on alliance, may be helpful. Some recent research has elaborated on therapeutic strategies and approaches that are specific to clients presenting with pathological narcissism (e.g., Yakeley, 2018;King et al, 2020;Weinberg and Ronningstam, 2020;Dimaggio, in press) with promising results. This research suggests that tackling dysfunctional representations of self and others; impairments in ability to self-reflect; lack of agency; use of dysfunctional coping methods and defenses; problems with empathy and an impaired ability to mentalise, may provide a basis for treatment of individuals with pathological narcissism.…”
Section: Discussionmentioning
confidence: 99%
“…A nuanced approach to narcissistic presentations, informed by tendencies towards grandiosity and/ or vulnerability, and awareness of their potential impact on alliance, may be helpful. Some recent research has elaborated on therapeutic strategies and approaches that are specific to clients presenting with pathological narcissism (e.g., Yakeley, 2018;King et al, 2020;Weinberg and Ronningstam, 2020;Dimaggio, in press) with promising results. This research suggests that tackling dysfunctional representations of self and others; impairments in ability to self-reflect; lack of agency; use of dysfunctional coping methods and defenses; problems with empathy and an impaired ability to mentalise, may provide a basis for treatment of individuals with pathological narcissism.…”
Section: Discussionmentioning
confidence: 99%
“…Previous studies have also shown that state-like components of alliance play a larger role in therapy outcome in patients who have “poor capabilities to form satisfying relationships with others” (Zilcha-Mano et al , 2019, p. 3). It has been argued that due to the nature of Cluster B personality disorders, this specific group of patients may have difficulty forming close attachments (Levy et al , 2010; Ronningstam, 2017; Weinberg and Ronningstam, 2020). It may thus be the case that this specific subgroup of patients may be less capable of the trait-like components of alliance, which have more influence on the short term therapy outcomes, but therapy outcomes are mostly predicted by state-like components of alliance.…”
Section: Discussionmentioning
confidence: 99%
“…However, it may well be that the relationship between therapy alliance and motivation and therapeutic outcome does not exist in the very specific population of forensic psychiatric patients with Cluster B personality disorders. As outlined earlier, the nature of these personality disorders may inhibit the formation of therapeutic alliance and treatment motivation or they may take a different form (Levy et al , 2010; Ronningstam, 2017; Weinberg and Ronningstam, 2020). The different nature of treatment alliance and treatment motivation may alter the relationship with treatment outcome.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…There is therefore a need for personalized and empirically validated treatments. The problem is that, as of today, there are none, in spite of NPD's wide prevalence, for example, 8.5%-20% in outpatient independent practice (Weinberg & Ronningstam, 2020).…”
mentioning
confidence: 99%